2020
DOI: 10.3390/md18090477
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Light Response of Skeletonema marinoi: Involvement of Ovothiol

Abstract: Diatoms are one of the most widespread groups of microalgae on Earth. They possess extraordinary metabolic capabilities, including a great ability to adapt to different light conditions. Recently, we have discovered that the diatom Skeletonema marinoi produces the natural antioxidant ovothiol B, until then identified only in clams. In this study, we investigated the light-dependent modulation of ovothiol biosynthesis in S. marinoi. Diatoms were exposed to different light conditions, ranging from prolonged dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…Without solar radiation, the generation of triplet states, radicals and ROS decreases, causing the decrease in OSH production as a response. In recent works [ 21 , 47 ], it has been shown that the expression of the gene encoding the key ovothiol biosynthetic enzyme, ovoA, in diatoms depends on the light conditions. The enhanced expression of ovoA under light irradiation can be explained as the need of its presence for both reduction of light-induced ROS and quenching of reactive triplet states.…”
Section: Discussionmentioning
confidence: 99%
“…Without solar radiation, the generation of triplet states, radicals and ROS decreases, causing the decrease in OSH production as a response. In recent works [ 21 , 47 ], it has been shown that the expression of the gene encoding the key ovothiol biosynthetic enzyme, ovoA, in diatoms depends on the light conditions. The enhanced expression of ovoA under light irradiation can be explained as the need of its presence for both reduction of light-induced ROS and quenching of reactive triplet states.…”
Section: Discussionmentioning
confidence: 99%
“…Pistelli et al previously reported that Skeletonema marinoi , Cyclotella cryptica , and Nannochloropsis oceanica coculture improved bioactive compound richness as vitamins and biomass augmented the antioxidant or chemoprotective activity [ 82 ]. The Skeletonema marinoi strain has also been studied for ovothiol biosynthesis, an efficient thiohistidine compound in the scavenging of radicals and peroxides and which has only been identified in clams [ 83 ]. Astaxanthin (a red secondary carotenoid) is denominated as a super antioxidant, and most of its production is carried out synthetically (95%); while the microalgae Haematococcus pluvialis is the natural source for this excellent compound.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Algae possess a complex enzymatic and non-enzymatic defense system to prevent photo-oxidative damage to cellular components. Enzymatic antioxidant protection includes three types of superoxide dismutases possessing different metal cofactors (CuZn-SOD, Fe-SOD, Mn-SOD), catalase, ascorbate peroxidase, glutathione peroxidase, while the non-enzymatic defense system includes ascorbic acid, glutathione, tocopherols, carotenoids, polyphenols, phycobilin proteins, dimethylsulfide/dimethylsulfoxide, sulfated polysaccharides [ 27 ], and sulfur-containing histidines such as ovothiols [ 28 , 29 ].…”
Section: Photo-damage/-protection Mechanisms In Marine Organismsmentioning
confidence: 99%
“…They are named ovothiols due to their high concentration in sea urchin eggs [ 147 ] and exhibit a characteristic absorbance spectrum (200–320 nm) with a maximum around 257 nm [ 148 ]. In addition, the gene expression of the key enzyme involved in their biosynthesis is modulated by several environmental factors, including exposure to metals and toxins in sea urchin embryos [ 149 ] and to high light in microalgae [ 29 ]. The light-induced modulation of ovothiol biosynthesis suggests their possible role in the protection of microalgae from light-induced stress.…”
Section: Other Potential Photoprotective Compounds Of Marine Originmentioning
confidence: 99%